Design, fabrication and Characterization of a 7 Litre Esterification Reactor - S. G., Wadzani; N. , Afulike; C. , Agu-Bruno; O. S., Ugwueze; R. U. , Imoh, (African Journal of Education,Science and Technology (AJEST), 2017)
The purpose of this research work is to characterize an Esterification Reactor (CSTR). The tracer experiments were carried out to validate the effectiveness of the reactor by using the beaker and stop watch method. Experimental data obtained at 0.6M of Nacl concentration and 160rpm gave a curve that is in close agreement to that of the model. In other words, the results obtained at a concentration of 0.6M and 160rpm is in close agreement with that of early researchers. Thus confirming the classification of the reactor as a CSTR. To carry the work further, an esterification process involving the reaction of ethanol and acetic acid catalyzed by sulfuric acid was chosen in this work. In this experiment, the direct synthesis of ethyl acetate was chosen. For a normal operation, the reactant concentration and catalyst concentration were set respectively to be 6M and 3M. The reaction was carried out at room temperature with 5% catalyst volume and without cooling water.